ASSESSING THE IMPACT OF ONLINE MEDICAL EDUCATION ON MEDICAL STUDENTS IN INDIA DURING THE COVID-19 PANDEMIC - Rajesh , Kumar Gupta; Sundaram, Meena Devi; Ananya, Mishra Srivastava (Global Journal of Medical and Health Science, 2023)
The COVID-19 pandemic necessitated a global shift towards online education, including in the field of medicine. In India, where a vast population resides in rural areas and network connectivity remains a challenge, the transition to online medical education posed unique challenges. This study, conducted at Dhanalakshmi Srinivasan Medical College, aimed to assess the impact of online medical education on Phase 4 (Final Year MBBS) medical students from December 2021 to March 2022. Our findings reveal that a significant portion of students were unaware of online teaching before the pandemic, and around 44% of students hailed from rural areas, where network issues were prevalent. This digital divide presented challenges, with over 60% of students spending more than 20 hours per week attending online classes. The lack of practical exposure, including bedside clinics and lab demonstrations, led to concerns about knowledge acquisition. Challenges cited by students included inadequate knowledge gain, limited rest between lectures, and network problems, especially in rural areas. Interestingly, about half of the students attended classes during travel, revealing a lack of engagement and responsibility. Despite these challenges, students highlighted opportunities offered by online education, such as increased comfort, reduced stress in the home environment, and the ability to record lectures for future reference. However, there was a consensus that face-to-face teaching might be necessary for high-quality learning, and interactive lecture classes were preferred over recorded videos. In conclusion, this study sheds light on the impact of online medical education in India during the pandemic. While online education offered certain advantages, including comfort and flexibility, challenges like limited practical exposure and network issues persisted. Addressing these challenges and striking a balance between online and offline teaching methods is crucial to ensure the effective education of medical students in India